Legalprotection for the Patent Registered by A Foreign Citizen in Indonesia Pursuant to the Law Number 13/2016 on Patent - Monalisa Lucky Maria Sinurat (CERED Indonesia Institute, 2022)
The registration of patent in Indonesia give a positive value to Indonesia’s economic growth because the bigger the number of patents in a country the higher the country’s capability to innovate. The government issues Law number 13/2016 on patents in order to protect the patents which have been registered in Indonesia so it is expected to motivate inventory, especially foreign citizens. In practice, those foreign citizen consider that article 20 of the Patent Law is a constraint because they are obligated to make products or follow the process applied in Indonesia, support the technology transfer, absorb the investment, and/or provide employment. Article 20 of patents law is also considered to violate the TRIP’s provisions. The government amends the patent law by issuing Law Number 11/20 on Job Creation but it crates a different positive law that is applied in Indonesia. The research problems are how about the development of invention registration for foreign citizen in the Directorate General of Intellectual Property during that last years, how about the benefits of giving legal protection for foreign citizen’s invention in Indonesia on Indonesia’s economic growth, and how about the legal implication ow Law Number 11/2020 on Job Creation on Patent Law, especially in relation to the grant of a patent for the invention of foreign citizen in Indonesia. The research method used is juridical normative method with a descriptive analyctical approach and the source of data is secondary data. The data collection technique is library research. The data are analyzed qualitatively and are obtained from the research result using deductive method. The result indicates that there is an increase by 25% in 2020. The legal protection for patents registered by foreign citizens can increase Indonesia’s economics condition due to employment opening, and an increase in knowledge and skill of Indonesias society. The application of Job Creation is considered not incaccordance with article 28 C Paragraph (1) of the Constitution of the Republic of Indonesia as the goal and purpose of forming the country.